The Appearance of Dark Triad Among University Students - Ujhelyi, Mária (International Journal of Engineering and Management Sciences, 2017)
In recent decades, the examination of the so called “Dark Triad” – narcissism Machiavellianism and psychopathy – occupies a prominent place in personality research. These socially undesirable characteristics, which, to some extent are present in everybody, can play an important role in the workplace. Dark Triad members are those, according to the literature who are strong in all three features. In my paper I will present the results of a study I conducted among the students of University of Debrecen Faculty of Economics and Business. I analyse the Dark Triad characteristics of students with the help of a validated measure the Dirty Dozen. In my research I try to find answer to what extent these personality traits appear in the examined sample? Is there any difference depending on the background variables (age, sex, educational programme ...)? Are my results consistent with those described in international research?